2016
DOI: 10.17221/182/2015-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycorrhizal inoculation of leek Allium porrum L. on mineral nitrogen leaching

Abstract: Kučová L., Záhora J., Pokluda R. (2016): Effect of mycorrhizal inoculation of leek Allium porrum L. on mineral nitrogen leaching. Hort. Sci. (Prague), This study evaluated the influence of the arbuscular mycorrhizal fungi (AMF) inoculation of leek (Allium porrum L.) on the leaching of ammonia and nitrate nitrogen from the experimental pots filled with either sterile or non-sterile soil mix, consisting equally of the arable soil and horticultural substrate. Leek plants were inoculated by Funneliformis mosseae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…AMF inoculation in field-grown tomato plants resulted in a nitrate content increase, consistent with the beneficial microorganism effect found in previous research [31]. Kučová [39] reported that AMF decrease nitrate leaching from soil.…”
Section: Resultssupporting
confidence: 88%
“…AMF inoculation in field-grown tomato plants resulted in a nitrate content increase, consistent with the beneficial microorganism effect found in previous research [31]. Kučová [39] reported that AMF decrease nitrate leaching from soil.…”
Section: Resultssupporting
confidence: 88%
“…In the present research, AMF inoculation resulted in a reduction of the bulb nitrate concentration both in garlic and onion; however, the latter effect was not recorded under the joint application AMF + Se. Other authors reported an improved plant assimilation of nitrogen, which enhances plant growth and development upon AMF inoculation [6,33] as well as the yield and quality of edible parts in Allium species [34,35]. Kucova et al [35] reported that AMF decrease nitrate leaching along the soil profile.…”
Section: Macroelementsmentioning
confidence: 99%
“…Other authors reported an improved plant assimilation of nitrogen, which enhances plant growth and development upon AMF inoculation [6,33] as well as the yield and quality of edible parts in Allium species [34,35]. Kucova et al [35] reported that AMF decrease nitrate leaching along the soil profile. The reduction of the nitrate concentration upon AMF inoculation in garlic and onion reflects the process of nitrate-reductase activation by these fungi [6,36].…”
Section: Macroelementsmentioning
confidence: 99%
“…[43] Funneliformis mosseae, Claroideoglomus claroideum, Rhizophagus intraradices AMF decreases nitrate leaching. [44] AMF + biochar Protection from heavy metals. Biochar decreases colonization degree of AMF.…”
Section: Allium Porrummentioning
confidence: 99%